2016
DOI: 10.17796/1053-4628-40.1.53
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Full-Mouth Rehabilitation on Oral Health-Related Quality of Life for Children with Special Health Care Needs

Abstract: Treating CSHCN under GA, with 3-month recall visits for the patients, had a significant long-term effect on their OHRQoL extending up to 12 months postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 18 publications
1
37
0
1
Order By: Relevance
“…In accordance with the inclusion and exclusion criteria, 11 articles were excluded. After evaluating the texts comprehensively, all 21 articles were included in the meta‐analysis . Within the same publication, one study contributed to the meta‐analysis twice because both the ECOHIS and COHRQoL questionnaires were used .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In accordance with the inclusion and exclusion criteria, 11 articles were excluded. After evaluating the texts comprehensively, all 21 articles were included in the meta‐analysis . Within the same publication, one study contributed to the meta‐analysis twice because both the ECOHIS and COHRQoL questionnaires were used .…”
Section: Resultsmentioning
confidence: 99%
“…Only five studies indicated the reasons for DGA, primarily due to fear, anxiety, and behavioural issues . All of the studies included healthy subjects with the exception of one study, which included patients with mental and physical disability . Patient socio‐economic status was not determined in any of the studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment of children with dental caries is usually a challenging procedure because the Pediatric dentist is required to possess operative skills as well as psychological management ones [1] . When the clinician is faced with uncooperative children, physical or mental disabled children, or ones with early childhood caries demanding more than multiple procedures, then one session treatment under GA seems to be an agreeable option [2] . The advantages of GA is to provide dental treatment in one setting with minimal psychological stress on the child.…”
Section: Introductionmentioning
confidence: 99%